Inhibitory Effect of L-Methionine-Modified Microcrystalline Cellulose on Gram-Positive Bacteria - WU Simiao, YANG Haifan, LIANG Guannan, SUN Xinyang (Shipin Kexue)
In order to effectively prevent and treat microbial contamination in foods, L-methionine-modified microcrystalline cellulose (M-MCC) with antibacterial effect was prepared by loading L-methionine (L-Met) on microcrystalline cellulose (MCC). The morphology, element composition and stability of M-MCC were characterized, indicating the successful grafting of L-Met. M-MCC had a good scavenging effect on 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cationic radicals, with a scavenging percentage of 97.47% at 20 mg/mL. M-MCC had a marked antibacterial activity against the Gram-positive bacteria Listeria monocytogenes and Staphylococcus aureus, with minimal inhibitory concentration and minimum bactericidal concentration of 15 and 30 mg/mL, respectively. Finally, the effect of M-MCC on the cell membrane permeability, cell membrane integrity, cellular contents and DNA content of the two bacteria was studied. The results showed that M-MCC treatment had a significant inhibitory effect on the growth of L. monocytogenes and S. aureus, and delayed the time taken to reach the logarithmic phase compared with the untreated group. Furthermore, it resulted in obvious changes in extracellular conductivity and the contents of nucleic acid and protein, which was closely related to the treatment time. This study shows that M-MCC has great application potential as an antibacterial agent.